Changes in the Health-related Quality of Life among Korean Adults: Data Comparison between 2007 and 2017 (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to analyze and compare changes in Koreans’ health-related quality of life between 2007 and 2017.Method/Statistical Analysis: A secondary analysis was conducted using raw data from 3,854 adults over 20 years old using the Korean National Health and Nutritional Examination Survey (KNHANES) statistics for 2007 and 2017.Findings: In 2007 the health-related quality of life (EQ-5D) among respondents was 0.97 and it was 0.98 in 2017, which indicated that there were not significant changes in this area. However, among other EQ-5D items, particularly with regard to anxiety and depression, there was a significant decrease noted in 2017 compared to 2007. In addition, socio-economic factors such as level of education and marital status affected health-related quality of life.Improvements/Applications: It is necessary to develop and manage policies that take into consideration factors affecting people’s health-related quality of life